2022
DOI: 10.1371/journal.pone.0274814
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effects of dried Moringa oleifera leaf extract on human Wharton’s Jelly mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) have seen an elevated use in clinical works like regenerative medicine. Its potential therapeutic properties increases when used in tandem with complementary agents like bio-based materials. Therefore, the present study is the first to investigate the cytotoxicity of a highly valued medicinal plant, Moringa oleifera, on human Wharton’s Jelly mesenchymal stem cells (hWJMSCs) and its effects on the cells’ gene expression when used as a pre-treatment agent in vitro. M. oleifera leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 93 publications
1
3
0
Order By: Relevance
“…Specifically, the intervention resulted in the up-regulation of numerous genes that are linked to cellular survival, such as those involved in DNA damage repair and cell cycle progression. A previous study demonstrated similar results in gene expression related to pathways associated with cell cycle progression, including CCNA , CCNB , CCND , PLK1 and CDC20 68 . In line with this, the present study demonstrated that fucoxanthin exhibited an up-regulation effect on TP53, a transcription factor that governs the genomic stability, proliferation, and differentiation of MSCs 18 .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Specifically, the intervention resulted in the up-regulation of numerous genes that are linked to cellular survival, such as those involved in DNA damage repair and cell cycle progression. A previous study demonstrated similar results in gene expression related to pathways associated with cell cycle progression, including CCNA , CCNB , CCND , PLK1 and CDC20 68 . In line with this, the present study demonstrated that fucoxanthin exhibited an up-regulation effect on TP53, a transcription factor that governs the genomic stability, proliferation, and differentiation of MSCs 18 .…”
Section: Discussionsupporting
confidence: 70%
“…The phenomenon of oxidative stress has the potential to damage DNA, leading to genetic instability in cells, ultimately resulting in cell cycle arrest and apoptosis 67 . Numerous studies have demonstrated that antioxidants possess the ability to protect against the detrimental impact of oxidative stress 68 , 69 . The present study employed a NanoString nCounter analysis to identify genes involved in metabolic pathways and showed that the administration of fucoxanthin affects the molecular profiling of PL-MSCs that were subjected to H 2 O 2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ramarao et al . (2022) reported that Moringa oleifera leaf extract containing phenolic compounds reduced the cell viability to below 80% of human Wharton's Jelly mesenchymal stem cells due to cell cycle arrest and induction of apoptosis at a dose level of 437.43 μg mL −1 . The pH of the media (7.4) was lowered to 6.8–7.0 when the concentration of the extract (water, methanol, ethanol and ethyl acetate) added to the media was 2000 μg mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Aside from this factor, the source of the plants may also be responsible for the difference in the effects obtained from these plant crude polysaccharides. Different parts of the Moringa species plants, especially the seeds, have been reported to show antiproliferative effects in many cancer cells [17,70,71], but the antiproliferative effects of extracted polysaccharides have not been documented. This study demonstrated that Moringa oleifera seed crude polysaccharides extracted through ethanol precipitation at 50% and 80% concentrations and room temperature were able to inhibit the growth of MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%